Dynamic changes in the home range of the subterranean rodent Myospalax baileyi - Zhou, Jianwei; Ji, Chengpeng; Dong, Kechi; Chu, Bin; Wang, Liqing; Hua, Limin (Frontiers in Ecology and Evolution, 2022)
As ecosystem engineers, subterranean rodents excavate and inhabit burrow systems. However, the changes in their use of underground space are poorly recorded. There is conflicting evidence about whether the burrow systems of subterranean rodents, once established, are relatively stable as a result of the high energy costs of digging. We monitored the size of the home ranges of the plateau zokor (Myospalax baileyi) during different stages of its life cycle to show whether mating behavior and the characteristics of its habitat influence the size and location of its home range. We used radio-tracking to quantify the changes in, and overlap of, the home range of M. baileyi during a one-year period. The average size of the home ranges of male zokors was 6.5 times larger than that of female zokors during the mating season. The males expanded their burrows to overlap with multiple females to increase their chances of mating. However, there was no overlap between estrus females or males, perhaps to reduce the number of encounters and unnecessary fights. The home ranges of male and female zokors were similar in size after courtship and the home ranges of single zokors overlapped with those of several neighbors. Most individuals remained territorial and excluded intraspecific interactions from their home ranges. The location of female zokors was stable throughout the year, but half of the males changed the location of their nests and established completely new home ranges in the non-breeding season, mainly in October. The use of space by M. baileyi is flexible in response to a need for physical contact during the mating season and food resources. The home ranges of subterranean plateau zokors are dynamic and the home ranges of male zokors can change within one breeding cycle.